Distribution of Al, Cd, Cu, Fe, Mn, Pb and Zn in Liver, Gills and Muscle of Early Life Stages of Atlantic Salmon (Salmo salar) - Lobos-Valenzuela, María Gabriela; Saez, Claudio A; Chavarria, Alejandra; Sepúlveda, Maritza; Díaz, Patricia; Gaete, Hernán (Bulletin of Environmental Contamination and Toxicology, 2021)
The aim of this study was to determine metal distribution in different tissues in early life stages of Atlantic salmon. The concentrations of the metals Al, Cd, Cu, Fe, Mn, Pb and Zn in liver, gills, muscle of fish and water from a salmon farm in the Region de los Lagos of southern Chile were determined. Results show that Cd and Pb had the lowest concentrations, while Zn the highest concentration, followed by Cu, Fe and Mn. Cu and Fe had the highest concentrations in liver, while Mn and Zn were the highest in gills. Cu and Fe in liver were higher in pre-smolts than in fingerlings. Cu had the highest bioaccumulation factor in pre-smolts, both in liver and gills. In conclusion the metals tend to bioaccumulate selectively in different tissues of Salmo salar. Liver is the most relevant for Cu and Fe, and liver and gills for Zn. Regular 2015 FONDECYT FONDECYT